Educational Values Found in The Film “The Blind Side” by John Lee Hancock - Wula, Yohanes; Jendra, Made Iwan Indrawan; Jayantini, I Gusti Agung Sri Rwa (Institut Pariwisata dan Bisnis Internasional, 2023)
Educational values are parts of life values that people can learn from many art works including films. The aim of this study is focused to analyze the types of educational values proposed of the “The Blind Side ” film. The analysis this research uses a qualitative method, This study applied the theory of Linda (1997). The educational values found in the “The Blind Side” film are honesty, courage, peace, ability, self-confidence and potential, self-discipline, pureness loyalty, trustworthiness, respect, love, compassion, sensitivity, unselfishness, kindness, and fairness. The result of this study showed that all types of educational values are found in the film “The Blind Side.” The most dominant of types of educational values in the film is Value of Being 7 (60%) data meanwhile, be the lowest dominant data is Value of giving with 5 (40%).